Analisis Pengaruh Sosial Ekonomi Terhadap Efisiensi Penggunaan Energi Listrik Sektor Rumah Tangga Di Sumatera Barat (Studi Kasus Daerah Perkotaan) - Sabri Sabri; Joan Marta; Selli Nelonda (Universitas Negeri Padang, 2022)
This study analyzes the socio-economic effect on the efficiency of electrical energy use in the urban household sector in West Sumatra (Urban Area Case Study) in 2020. The results of this study explain that the variables of per capita expenditure, education, employment status, age, and communication technology have a positive effect on the intensity of electrical energy use. While the variable of building ownership status is the only variable that has a negative effect on the intensity of electricity use in the urban household sector in West Sumatra. The decrease in the intensity of the use of electrical energy in the urban household sector in West Sumatra reflects the condition of efficiency in the use of electrical energy. On the other hand, the increase in the intensity of use of electrical energy in the urban household sector in West Sumatra reflects conditions in the efficient use of electrical energy.